Pengaruh Motivasi dan Kedisplinan Kerja terhadap Prestasi Kerja Karyawan pada PT. Karyamitra Budisentosa Bagian Warehouse Pandaan Pasuruan - Peni Indrawati; Yahya Teguh Ismawanto (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2021)
The aim of this study was to determine the effect of motivation and work discipline on employee performance. In this research, the respondents are employees who work at PT. Karyamitra Budisentosa in the Warehouse (department) with the number of employee personnel as many as 30 people and the research sample usedas many as 30 people. The data used in this study is primary dataobtained by distributing questionnaires to employees in theWarehouse PT. Karyamitra Budisentosa Pandaan Pasuruan. From the results of this study, the analytical technique used is multiple linear regression analysis using the F test hypothesis test and t test with a significance level of 5%. The test results prove that the variables of motivation and work discipline have a simultaneous and partial effect on the work performance of employees in the Warehouse section of PT. Karyamitra Budisentosa Pandaan with F count > F table value and tcount > t table value, while the motivation variable has a dominant effect on employee performance. Keywords: Motivation, Work Discipline and Work Achievement